Nursing perception of the quality of emergency triage - Thamy Caamano Droguett; Meiry Fernanda Pinto Okuno; Cassia Regina Vancini Campanharo; Maria Carolina Barbosa Teixeira Lopes; Ruth Ester Assayag Batista (Universidade Federal de Santa Maria, 2018)
Aim: to evaluate the quality of triage in an emergency service according to the perception of the nursing professionals. Method: a cross-sectional study carried out at the emergency service triage of the São Paulo Hospital, between March and July 2016. A hundred and thirty-three professionals who worked in the sector for at least three months participated in the study. A questionnaire was used with variables for sociodemographic characterization and, also, an instrument for triage quality evaluation. Results: mean age 36.2 years, the majority of females (77.4%) and graduated for more than 5 years (59.1%). The triage obtained the following scores: structure (23.0), process (22.0) and result (20.9). Conclusion: the triage quality was evaluated as precarious in the perception of the nursing professionals.